Achievements and challenges of research and development activity as one of the pillars of Knowledge Triangle in the Republic of Moldova - Rodica CRUDU (Eastern European Journal of Regional Studies, 2015)
In a very short period, economic globalization has changed the world economic order, creating new challenges but also new possibilities. Moldova can not be competitive in this new context, unless it becomes more innovative and responds more efficiently to the consumer needs and preferences. Taking in consideration the remittances and consumption as a result, are unable to fuel long-term economic growth of Moldova, we need a new paradigm of development that would increase based smart investment, innovation and competitiveness. During the 20 years of reform in Moldova, state policies have undergone into an essential metamorphosis: priorities have evolved gradually from fundamental science and military necessities to industrial and key technologies. Currently, it outlines a new stage, focusing on innovation and societal needs as a whole. An analysis of the sources of growth in Moldova in a classical representation of the production function Cob-Douglas suggests a very alarming conclusion - without a serious effort to change the paradigm of development, growth potential in the next 10 years is limited to a up to 4, 5% to 5% per year.